Analisis Dan Perancangan Sistem Informasi Toko Alat Tulis Kator (Studi Kasus: Toko Amarta) - Priskila, Ressa; Damayanti, Novrina (Universitas Palangka Raya, 2022)
Toko Amarta is an office stationery store that, in the process of recording transactions of goods, still uses manual methods. This often results in errors in recording data on the number of incoming and outgoing goods as well as the number of stocks. To overcome these problems, an office stationery transaction data processing system was created at the Amarta Store by utilizing technology-based software that can be expected to help realize a fast, accurate, and accountable system, namely a website-based office stationery shop information system. The method used in making this information system is the waterfall method. System business processes are depicted with flowcharts, and for system modeling, with Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD). The programming languages used are HTML, PHP, CSS, Bootstrap, JavaScript, and MySQL. On this website, there are several features, namely product data, stock data, sales data, and purchase data. With this information system, store owners can manage store data centrally.